Incidencia de la aplicación de las Normas Internacionales de Información Financiera en el análisis financiero de las empresas del sector retail inscritas en la Bolsa de Valores de Lima año 2018 - Horna Gil, Yanet Celestina (2019)
The purpose of this research is to determine the incidence of International Financial Reporting Standards in the financial analysis of retail sector companies registered in the Lima Stock Exchange year 2018, with the main objective of identifying whether the application of the of International Financial Reporting Standards has had a favorable or unfavorable impact on the financial analysis of companies in the retail sector. As specific objectives, it seeks to describe the financial and economic situation through the financial analysis of the companies of the retail sector that are listed on the Lima Stock Exchange in fiscal year 2018 and identify the effect of the application of IFRS in the financial analysis and in the calculation of the financial indicators. This research has as a universe and as selected sample, the companies Saga Falabella S.A. and Supermercados Peruanos S.A. in the year 2018. The type of research according to the purpose is Descriptive and according to the Nonexperimental Design - Causal Correlational. Similarly, the techniques used have been the documentary and financial analysis of the information obtained, and the tabulation of tables in quantities and percentages. Through the research carried out, results have been achieved, which prove that the application of IFRS has a favorable impact on profitability and EBITDA but negatively on liquidity and indebtedness indicators of companies in the retail sector that shape the sample.